SVG and Arabic font challenges and improvements - Taha, Imad; Alahmad, Mohammad (2013)
we investigate SVG usage to display Arabic font on the web. SVG (Scalable Vector Graphics) is a standard applied widely over several applications. It can be used to display vector graphics and text on web pages. SVG has witnessed several improvements and drew more attention as the devices used to surf the web are evolving in screen sizes and resolutions. This paper demonstrates how to convert normal font to SVG, then opens the opportunity for an engine that can render Arabic SVG font on different platforms and ends with challenges and solutions for them. We speculate that SVG will play great rule in future technologies and making use of it early on can lead to great benefits for Arabic language consumption over the web.